Fibromyalgia in patients with migraine: A literature review in the last 20 years - Fortes, Yasmine Maria Leódido (2022)
IntroductionPossibly fibromyalgia and migraine share similar pathophysiological mechanisms, generatingan imbalance of neurotransmitters involved in pain modulation, with increased neuronal excitability. The association between these two conditions is frequent, increasing the disability of both.ObjectivesWe aimed to review articles published in the last 20 years about the presence of fibromyalgiain patients with migraine and to analyze the quality of life of these patients.MethodsBased on a literature search in the major medical databases and using the descriptors “migraine” and “fibromyalgia” we include articles published between 2001 and 2021. We found 387 articles, but only five met the inclusion criteria.ResultsIn five articles analyzed, 429 patients with migraine were found, in which fibromyalgiawas present in 31.5% of them, predominantly in women (p<0.0001). In this association, there was a higher risk for depression and worse quality of life.ConclusionsThe association of fibromyalgia in patients with migraine is frequent, increasing the disabilityof these two diseases and generating great social impact. Knowledge of this association and the management of its consequences are necessary in medical practice.